Antihyperglycemic, antioxidant activities of tucumã oil (Astrocaryum vulgare) in alloxan-induced diabetic mice, and identification of fatty acid profile by gas chromatograph: New natural source to treat hyperglycemia. (25th May 2017) - Baldissera, Matheus D.; Souza, Carine F.; Grando, Thirssa H.; Cossetin, Luciana F.; Sagrillo, Michele R.; Nascimento, Kátia; da Silva, Aleksandro S.; Machado, Alencar K.; da Cruz, Ivana B.M.; Stefani, Lenita M.; Klein, Bruna; Wagner, Roger; et al.
Abstract: The aim of the study was to investigate the effect of the oral administration of tucumã oil ( Astrocaryum vulgare ) on glucose and insulin levels, oxidative status, and pancreatic genotoxic parameters of alloxan-induced diabetic mice. The animals were divided into four groups (n = 6 each): control/water; control/tucumã oil; diabetic/water; diabetic/tucumã oil treated for 14 days with 5.0 mL kg −1 via oral gavage. Gas chromatograph characterization demonstrated that oleic/elaidic fatty acid is the most abundant component present in this oil, followed by palmitic and stearic fatty acids. Our results demonstrated an increase ( p < 0.05) in water and food intake, blood glucose, thiobarbituric acid reactive species (TBARS) levels, damage index, and frequency of damage; conversely body weight, insulin levels, catalase (CAT) and superoxide dismutase (SOD) activities, and cell viability were decreased in the diabetic/water group compared to the control/water group. The treatment with tucumã oil prevented these alterations in the diabetic/tucumã oil group compared to the diabetic/water group, and restored these parameters near to the control/water group. In summary, our findings demonstrated that treatment with tucumã oil causes a hypoglycemic effect improving insulin levels and antioxidant/oxidant status, and has a protector effect against pancreatic damage induced by oxidative stress in alloxan-induced diabetic mice. Graphical abstract: Highlights: Tucumã oil significantly improves glycemic status. Tucumã oil ameliorate enzymatic antioxidant defenses and to prevent lipid peroxidation. Tucumã oil has hypoglycemic effect by improving insulin levels. Oleic/elaidic fatty acid is the principal compound present in tucumã oil. Tucumã oil may be considered an important alternative to treat hyperglycemia.